Measurement of the ratio of branching fractions B(B+c→J/ψK+)/B(B+c→J/ψπ+) - Cheung, S; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Hill, D; Jalocha, P; John, M; Lupton, O; Malde, S; Nandi, A; Topp-Joergenson, S; et al. (Springer, 2016)
The ratio of branching fractions RK/π ≡ ℬ(Bc+ → J/ψK+)/ℬ(Bc+ → J/ψπ+) is measured with pp collision data collected by the LHCb experiment at centre-of-mass energies of 7 TeV and 8 TeV, corresponding to an integrated luminosity of 3 fb−1. It is found to be RK/π = 0.079 ± 0.007 ± 0.003, where the first uncertainty is statistical and the second is systematic. This measurement is consistent with the previous LHCb result, while the uncertainties are significantly reduced.